Guidance Surface to Help Vision-Disabled Pedestrians Locate Crosswalks and Align to Cross. Issue 10 (October 2022) - Bentzen, Billie Louise; Scott, Alan C.; Barlow, Janet M.; Emerson, Robert Wall; Graham, Jennifer
Raised-bar guidance surfaces (GSs) are used internationally to help wayfinding by vision-disabled pedestrians, but they are little used in the United States. However, difficulties experienced by vision-disabled pedestrians in locating crosswalks and aligning to cross have been documented, and the installation of GSs with bars perpendicular to the crossing direction has been shown to improve locating the crosswalk and aligning to cross at noncorner crossings. The present research investigated the effect, for a total of 68 participants, of a raised-bar GS on locating crosswalks and aligning to cross at (primarily) corner crossings in three cities. Using 2- × 2-ft raised-bar GSs with bars oriented perpendicular to the crossing direction at corner crossings, and a 2-ft wide strip of GSs extending across the sidewalk at noncorner crossings, significant improvements in the accuracy of crossing starting position and alignment were observed. Accuracy in locating the crosswalk was quite good at corner crossings, and was not improved by the GS. Installation of a raised-bar GS with bars perpendicular to the crossing direction is recommended to help vision-disabled pedestrians align for crossing. At corner crossings, a 2- × 2-ft GS located beside the detectable warning surface at the bottom of curb ramps, on the side farthest from the intersection, is recommended. At noncorner crossings, a 2-ft wide strip of GS extending all the way across the sidewalk, with the bars oriented perpendicular to the crossing direction, is recommended.